Profile of Culture-Based Career Adaptability of Students - Rindanah, Rina (Departemen Psikologi Pendidikan dan Bimbingan FIP Universitas Pendidikan Indonesia, 2018)
The aim of this study is to find out the profile of student career adaptability based on culture where culture influences individual personality. Culture contributes to differences in character between individuals with each other. This research was conducted at IAIN Sheikh Nurjati Cirebon, where students are very heterogeneous which is very likely to influence the adaptability of his career. In this study focused on how the career adaptability of students with different backgrounds, namely students from ethnic Sundanese and students from ethnic Javanese. The research was conducted with quantitative methods of analytic survey type, namely to capture the career adaptability of students with their type of research using Exploratory Type. The results showed that the level of career adaptability of students from Java was higher compared to students from Sundanese with detailed scores: Student career adaptability from Java in the high category was 27 people (54%), moderate category was 21 people (42 %) and in the low category as many as 2 people (4%). While the career adaptability of students from the Sundanese is in the high category as many as 16 people (32%), the moderate category is 31 people (62%), and in the low category there are 3 people (6%).